MAJOR, TRACE ELEMENT AND ND-SR-PB-O-HE-AR ISOTOPE SIGNATURES OF SHIELD STAGE LAVAS FROM THE CENTRAL AND WESTERN CANARY ISLANDS: INSIGHTS INTO MANTLE AND CRUSTAL PROCESSES - Gurenko A.A.; Hoernle K.A.; Hauff F.; Schmincke H.U.; Han D.; Miura Y.N.; Kaneoka I. (My University, 2006)
The Canary plume is one of the few plumes that can be traced to the core-mantle boundary, making it an excellent location for studying mantle melting dynamics. We performed a comprehensive study of the subaerial shield stage lavas erupted on Gran Canaria, Tenerife, La Gomera and La Palma because these rocks are believed to have been formed by the greatest degree of partial melting of the source and thus can provide direct insights into the origin of plume material and deep crustal recycling. The most primitive picritic to alkali basaltic and basanitic shield stage lavas are moderately enriched in light rare earth elements ([La/Sm]n = 2.1-4.6), strongly enriched in Nb and Ta ([Nb/La]n = 0.8-1.5, [Ta/La]n = 1.3-1.8) and depleted in K and Pb ([K/La]n = 0.2-0.7; [Pb/La]n = 0.2-0.3), resembling HIMU-type magmas. Fractional crystallization and phenocryst accumulation are processes affecting the compositions of parental magmas. The Sr-Nd-Pb isotope data (87Sr/86Sr = 0.702966-0.703312, 143Nd/144Nd = 0.512884-0.512929, 206Pb/204Pb = 19.49-20.27, 207Pb/204Pb = 15.59-15.66, 208Pb/204Pb = 39.21-39.81) and the relationship between Sr isotopes in whole rocks and O isotopes in olivine phenocrysts (δ18O = 4.3-5.8 ± 0.3‰) argue against extensive magma contamination at crustal depths. Varying, but relatively low, degrees of partial melting (1-10%) of a peridotite source containing 2-20% garnet can explain the Zr/Y range between 6.7 and 10.3 but require unrealistically high amount of garnet (up to 30%) to account for higher (up to 11.8) Zr/Y ratios in the lavas from Gran Canaria. This observation, as well as systematically lower CaO/Al2O3 ratios, higher SiO2 and NiO contents at a given MgO in the Gran Canaria lavas, as compared with those from other Canary Islands, imply melting of a plume probably containing garnet-bearing recycled component in a form of eclogite. The presence of amphibole and/or phlogopite is essential to produce variations in Ba/Nb (3.6-7.7), Ba/Th (51-108), K/La (65-295) and Nb/U (42-85) ratios in the shield stage magmas. We propose a scenario in which the magmas are derived through partial melting of a plume probably containing a recycled component with "ghost" amphibole and/or phlogopite signature; fluid-mobile elements compatible in amphibole and phlogopite could be preferentially lost to the subarc mantle during subduction-related breakdown of these phases. The relationships between He (3He/4He = 5.7-9.3 RA), Nd, Sr and Pb isotope ratios support the presence of a recycled component in the source of the Canary shield stage magmas. The observed relatively low 40Ar/36Ar isotopic ratios between ~ 310 and ~ 450 indicate contamination of plume-derived magmas by atmospheric air. © 2006 Elsevier B.V. All rights reserved.
Keywords: CANARY ISLANDS; MANTLE PLUME; NOBLE GASES; RADIOGENIC ISOTOPES; TRACE ELEMENTS